Electrically Responsive Shape Memory Composites Using Silver Plated Chopped Carbon Fiber - Wang, Yongkun; Chen, Zhenhong; Niu, Jiahao; Shi, Yang; Zhao, Jiangpeng; Ye, Junjie; Tian, Wenchao (Frontiers in Chemistry, 2020)
High electrical and thermal conductivity is beneficial to shape recovery performances of electroactive shape memory polymer composites. In this work, the chopped carbon fiber (CCF) was processed into silver plated chopped carbon fiber (Ag/CCF), and the Ag/CCF was filled into hydro-epoxy (H-EP) resin to prepare the electrically responsive shape memory composites. The Ag/CCF/H-EP composites show good electrical and thermal conductivity compared to the CCF/H-EP composites. When the content of Ag/CCF reaches 1.8 wt%, the e Ag/CCF/H-EP composites reach the threshold of thermal conductivity, electrical conductivity and percolation. The thermal conductivity of H-EP composite with 5.4 wt% Ag/CCF is 2.33 W/(m·K), which is 2.6 times and 12 times of that of CCF/H-EP composite and H-EP matrix respectively. When the content of Ag/CCF reaches 7.2 wt%, the volume resistivity and surface resistivity of Ag/CCF/H-EP composites decrease from 1.7 × 1016 Ω· cm and 6.9 × 1015 Ω to 9.5 × 103 Ω· cm and 6.2 × 102 Ω, respectively. And the Ag/CCF/H-EP composites show good mechanical properties and dynamic thermomechanical properties. When the content of Ag/CCF is more than 1.8 wt%, the Ag/CCF/H-EP composites exhibit excellent electroactive shape memory performance, and the shape recovery rate of the composites are more than 92%.